Comparative morphology of gonads from six species of fish belonging to the family Anostomidae (Characiformes: Anostomidae) - Arantes, Fabio Pereira (2017)
In fishes, gonad morphology is an important parameter to understand the reproductive biology, phylogenetic relationships and systematic studies. The main objective of this study was to make a comparative analysis of the morphology of mature ovary and testis in six fish species of the family Anostomidae. A total of 212 specimens, presenting maturing gonads, were captured from the São Francisco River, Três Marias Reservoir area, in Southeastern Brazil, between August 2008 and December 2010. The six analyzed species had mature ovaries and showed a grayish color. In vitellogenic oocytes (VO), cortical alveoli (CA) were composed by small vesicles in all Leporinus species, but in Leporellus vittatus and Schizodon knerii the CA were large vesicles. However, the CA of all species showed similar histochemical content. The pellucid zone consists of two layers to all species, but it was thicker in S. knerii (11.5 ± 1.8 µm) than in L. vittatus (9.0 ± 0.8 µm) and Leporinus species (3.5 ± 0.6 - 8.7 ± 0.9 µm). Follicular cells of the VO were respectively cubic and prismatic in animal and vegetative poles of S. knerii (22.3 ± 3.2 and 61.1 ± 9.6 µm), and squamous in the other species (1.3 ± 0.3 - 1.6 ± 0.3 µm). Females of S. knerii and males of L. vittatus showed lower values of gonadosomatic index (GSI) than the other assessed species. All evaluated species presented testicular morphology similar to most neotropical Characiformes, with unrestricted spermatogonial testis and anastomosing tubular organization of seminiferous tubules. Phenotypical differences in the vitellogenic oocyte of Anostomidae fishes, confirmed the taxonomic position of S. knerii as different genus in relation to Leporinus and L. vittatus. Despite being placed in different genera, the characteristics of the vitellogenic oocytes of L. vittatus were similar to those found in the studied Leporinus.